Commercial System for Soilless production of Pharmaceuticals plants - Iliev, Tome; Pernica, Karel; Honcová, Martina; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
Abstract:Begun in the 20th century, aeroponics was a developing project that mainly focused on planting without the use of soil. This innovation became more and more popular in the beginning of the 21st century and has been developing ever since. The main purpose of this thesis is to create a business plan for a star up that will implement the idea of aeroponics systems in the Czech Republic. The paper includes a theoretical part along with a practical part; where in the theoretical part an extensive explanation was conducted to explain all the different sections that will be deeply analyzed in the practical part. The practical part placed the theory into practice and this included an executive summary, business opportunities analysis, the business overview, market and competition analysis, VRIO analysis, SWOT analysis, scenario planning, marketing plan and the financial plan. After the extensive examination of the business plan the company is convinced that such a project can be implemented in the Czech Republic and will benefit the country in different ways.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses